The Influence of Organizational Culture, Organizational Commitment to Fraud Prevention with Internal Control as an Intervening Variable in the South Sumatra Provincial Government - Putri, Intan Femizah; Rachman, Andry Arifian (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2024)
This study aims to test and analyze the influence of organizational culture and organizational commitment to fraud prevention with internal control control as an intervening variable. The data collection method used a survey using a questionnaire. The population in this study is part of the South Sumatra Provincial Government's procurement of goods and services. The sampling technique uses the purposive sampling technique. The number of respondents was 136 from 30 regional apparatus organizations (OPD) that were sampled. The data analysis method used in the study was PLS SEM. The results of this study show that organizational culture and commitment have a positive and significant effect on fraud prevention, with an R Square value of 97.5%. The results of this study also show that organizational culture, organizational commitment, and internal control have a positive and significant effect on internal control, with an R Square value of 93.4%. The results of this study provide empirical evidence that fraud prevention can be carried out with organizational culture and organizational commitments and good internal control so that fraud does not occur.